Vaginal Microbiota and Cytokine Microenvironment in HPV Clearance/Persistence in Women Surgically Treated for Cervical Intraepithelial Neoplasia: An Observational Prospective Study - Caselli, Elisabetta; D’Accolti, Maria; Santi, Erica; Soffritti, Irene; Conzadori, Sara; Mazzacane, Sante; Greco, Pantaleo; Contini, Carlo; Bonaccorsi, Gloria (Frontiers in Cellular and Infection Microbiology, 2020)
High-risk human papillomaviruses (hrHPVs) are causally related to cervical intraepithelial neoplasia (CIN) and subsequent cervical cancer (CC). The vaginal microbiome has been suggested to play a role in the development of CC, but the effect of conservative surgical treatment on the microbiome and hrHPV elimination has not been elucidated. In this study, we aimed to characterize the vaginal microbiome and inflammatory chemokine profile in 85 women treated for CIN2-CIN3 lesions, before and after surgical CIN removal. The results showed, as expected, a high prevalence of dysbiotic microbiomes and vaginal pro-inflammatory cytokines in the CIN cohort, correlated with disease severity, at the basal level. By contrast, surgical CIN removal induced significant vaginal microbiome variations, and specific microbiome/cytokine profiles were associated with hrHPV clearance/persistence at 6-month follow-up. hrHPV-cleared patients, in fact, showed a specific increase of L. crispatus and decrease of dysbiosis and inflammatory cytokines compared to hrHPV-persistent patients. These data highlight the crosstalk between HPV and the local microbiome, and suggest that vaginal microbiome modulation might represent a novel approach to modifying the natural history of hrHPV-related CC. Study registration n. ISRCTN34437150 (https://www.isrctn.com/ISRCTN34437150).